Oxidative stress in acute pulmonary embolism: emerging roles and therapeutic implications - Jingchao Yang; Jinzhu Xu; Shuanglan Xu; Zeqin Fan; Chenshao Zhu; Jianyuan Wan; Jiao Yang; Xiqian Xing (Thrombosis Journal, 2024)
Abstract Oxidative stress is an imbalance between the body’s reactive oxygen species and antioxidant defense mechanisms. Oxidative stress is involved in the development of several cardiovascular diseases, such as pulmonary hypertension, atherosclerosis, and diabetes mellitus. A growing number of studies have suggested the potential role of oxidative stress in the pathogenesis of pulmonary embolism. Biomarkers of oxidative stress in pulmonary embolism have also been explored, such as matrix metalloproteinases, asymmetric dimethylarginine, and neutrophil/lymphocyte ratio. Here, we comprehensively summarize some oxidative stress mechanisms and biomarkers in the development of acute pulmonary embolism and summarize related treatments based on antioxidant stress to explore effective treatment strategies for acute pulmonary embolism.